A Unified theory of plastic buckling of columns and plates - Stowell, Elbridge Z. (National Advisory Committee for Aeronautics, 1948)
On the basis of modern plasticity considerations, a unified theory of plastic buckling applicable to both columns and plates has been developed. For uniform compression, the theory shows shows that long columns which bend without appreciable twisting require the tangent modulus and that long flanges which twist without appreciable bending require the secant modulus. Structures that both bend and twist when they buckle require a modulus which is a combination of the secant modulus and the tangent modulus.
"April 1948."
NACA TN No. 1556.
Keywords: Columns.; Plates (Engineering); Buckling (Mechanics); Mathematical analysis.; elektronické knihy; electronic books